Case report: A case of abrupt stroke as the first symptom of neurobrucellosis - Liu, Ying; Gu, Yan (Frontiers in Neurology, 2023)
Acute cerebral infarction caused by small artery inflammatory disease, which is triggered by neurobrucellosis, is a rare condition that can be easily misdiagnosed. Neurobrucellosis is a rare complication of brucellosis that can present clinically as meningitis, meningoencephalitis, myelitis, neuritis, or psychosis. In this study, we report the case of a patient with neurobrucellosis who was hospitalized in the First People's Hospital of Lianyungang in September 2022; the primary symptom was weakness in the left limb for 14 h. The patient was discharged after receiving symptomatic and anti-Brucella medication.